Tea in Chinese Idioms: Reflecting Cultural Values in Chinese Society - Hansakulwat, Kamolrat (Parichart Journal, 2025)
This research article aimed to achieve two primary objectives. First, it explored the reflection of cultural values in Chinese society through Chinese proverbs that included the term "Tea" (茶). Second, it analyzed the linguistic meanings of these proverbs featuring "Tea" (茶) by compiling data from both physical and digital dictionaries of Chinese vocabulary and idioms, totaling 103 proverbs. The analysis employed a framework of linguistic meaning analysis within the theory of conceptual metaphor. The findings revealed that Chinese proverbs containing the term "Tea" reflected diverse cultural values in Chinese society, which could be categorized into six themes: 1) economic value and significance in Chinese life, 2) values associated with traditions and important rituals, 3) values related to hospitality and friendship, 4) beliefs regarding the medicinal properties of tea, 5) life philosophy, and 6) temporal aspects. Furthermore, the researcher interpreted metaphorical meanings as a transfer of meaning from the intrinsic qualities of the term "tea" to its broader implications, which could be classified into two groups: [humans as tea] and [inanimate objects as tea]. This categorization illustrated the Chinese conceptualization that compared tea to human experiences and various elements of life, encompassing emotions, actions, objects, and time.